KARAKTERISASI SIFAT FISIKO KIMIA TEPUNG BUAH NIPAH ASAL KABUPATEN ROKAN HILIR PROVINSI RIAU - Hairul Adhe Agams; Usman ' Pato; Rahmayuni ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to obtain the best composition of the nutritional value of the flour produced from the different ripeness of nipa palm fruit. This study used a completely randomized design (CRD) with three treatments and five replications. The treatments were T1 (Nipa palm fruit with the ripeness level of young). T2 (Nipa palm fruit with the ripeness level of a bit old). T3 (Nipa palm fruit with the ripeness level of old). Results of analysis of variance showed that the degree of ripeness of nipa palm fruit significantly affected the moisture, ash, fat, protein, fiber and starch contents of the flour produced. Based on the results of the physical and chemical analysis, T2 (Nipa palm fruit with the ripeness level of a bit old) was selected as the best treatment with moisture content of 13.57%, ash 2.22%, fat 0,06%, protein 6,39%, fiber 20.19%, starch content 61.53% and flour with natural white colour.   Keyword : Nipa palm, flour, physical and chemical characterization, Rokan Hilir